General practitioners’ attitudes and decision making regarding admission for older adults with infection: a UK qualitative interview study - Moore, A; Croxson, C; McKelvie, S; Lasserson, D; Hayward, G (Oxford University Press, 2018)
Background The world has an ageing population. Infection is common in older adults; serious infection has a high mortality rate and is associated with unplanned admissions. In the UK, general practitioners (GPs) must identify which older patients require admission to hospital and provide appropriate care and support for those staying at home. Objectives To explore attitudes of UK GPs towards referring older patients with suspected infection to hospital, how they weigh up the decision to admit against the alternatives and how alternatives to admission could be made more effective. Methods. Qualitative study using semi-structured interviews. GPs were purposively sampled from across the UK to achieve maximum variation in terms of GP role, experience and practice population. Interview transcripts were coded and analysed using a modified framework approach. Results GPs’ key influences on decision making were grouped into patient, GP and system factors. Patient factors included clinical factors, social factors and shared decision making. GP factors included gut instinct, risk management and acknowledging an associated personal emotional burden. System factors involved weighing up the pressure on secondary care beds against increasing GP workload. GPs described that finding an alternative to admission could be more time consuming, complex to arrange or were restricted by lack of capacity. Conclusion GPs need to be empowered to make safe decisions about place of care for older adults with suspected infection. This may mean developing strategies to support decision making as well as improving the ease of access to, and capacity of, any alternatives to admission.